"Fighting Larry" - Defender of the Faith?: Rev. Dr J. Laurence Rentoul (1845-1926) - Ward, Rowland (Reformed theological review, 2025)
The Rev. Dr J. Laurence Rentoul was the outstanding leader and theological educator in the Presbyterian Church of Victoria for over 40 years. Belonging to an extended family of numerous Presbyterian ministers in Ireland, he regarded himself as an "evangelical broad churchman" and was able to steer the church away from modernist assumptions without committing to strict orthodoxy. He was a controversialist who opposed oppression by various powerful vested interests. The accusations of some inconsistency in his approach to issues, such as Roman Catholicism or war, fail to reflect sufficiently on his complex background and experiences in Ireland.